Ten New Additions to the Flora of Chhattisgarh, India - Mishra, Rajendra Prasad; Naik, M. L.; Tiwari, Arjun Prasad; Pandey, Arun Kumar (Indian Forester, 2023)
The present paper deals with ten angiosperms namely Alocasia decipiens, Breynia retusa, Cosmostigma racemosum, Dinebra polystachyos, Dracaena terniflora, Gamphostemma parviflorum, Gymnema inodorum, Huberantha cerasoides, Lepisanthes tetraphylla and Solanum erianthium as new Distributional record for Chhattisgarh state. The nomenclature with taxonomic citation, description, phenology, distribution, locality of occurrence and field number of each taxon are provided. In addition to this colour photographs of each species are also provided.